2013
DOI: 10.1179/1743288x13y.0000000084
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave therapy as a treatment for heterotopic ossification

Abstract: Background: Extracorporeal shock wave therapy (ESWT) is an intervention treatment in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, to judge the effect of RSWT on NHO, quantifications like three-dimensional CT were also neglected apart from simple X-ray. Also we applied 2,500 shocks of 3.0 bars for six sessions, which is a higher number of treatment sessions compared to previous studies [ 4 ], which might have increased the bleeding risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, to judge the effect of RSWT on NHO, quantifications like three-dimensional CT were also neglected apart from simple X-ray. Also we applied 2,500 shocks of 3.0 bars for six sessions, which is a higher number of treatment sessions compared to previous studies [ 4 ], which might have increased the bleeding risks.…”
Section: Discussionmentioning
confidence: 99%
“…Serum alkaline phosphatase (ALP) levels had almost normalized and no further progression of NHO was noted. Therefore, we decided to apply RSWT on chronic NHO according to previous reports [ 4 5 ]. Etidronate disodium and NSAID had been discontinued one week prior to RSWT.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Plain X-ray of the right hip was done and revealed HO at greater trochanter and femoral head with long axis length for greater trochanter HO 37.3 mm seems desirable to find ways of either preventing or treating this pathological process for improved rehabilitation. There are several studies reported, where ESWT was effective in relieving pain caused by mature HO [5], [6].…”
Section: Case Presentationmentioning
confidence: 99%
“…Neurogenic heterotopic ossification (NHO) is a complication of a neurological injury, with ossification often affecting major synovial joints such as the hip or knee [2,3] . NHO is particularly found in patients following traumatic brain injury (TBI), with an estimated prevalence of between 3% and 23% [4][5][6] . NHO typically develops within two to four months of the initial trauma and manifests itself clinically as swelling, erythema, warmth, and severe pain [7] .…”
Section: Introductionmentioning
confidence: 99%